2017
DOI: 10.1590/0103-8478cr20170085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EGF receptors in canine prostate with proliferative inflammatory atrophy and carcinoma

Abstract: Gene expression of ErbB1 and ErbB2, and immunostaining of EGFR (Her1) and Her2 (c-erbB-2) were evaluated in this study to ascertain whether these receptors are involved in the evolution of canine premalignant and malignant prostatic lesions, as proliferative inflammatory atrophy (PIA) and prostatic carcinoma (PC). With regards to the intensity of EGFR immunostaining, there was no difference between normal prostatic tissue and tissues with PIA or PC. In relation to Her2 immunostaining, there were differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As Ki67, HER1, and HER2, members of the epidermal growth factor receptor (HER) family are also up regulated in prostate cancer [ 111 , 112 ]. Reports have indicated a gain in the number of copies of the HER2 gene, which results in frequent overexpression of the protein not only in prostate tumors [ 113 ] but also in PIA [ 111 ]. Faleiro et al [ 111 ] detected mRNA of the HER1 gene in all evaluated cases of canine PC although present in normal tissue and pre-neoplastic lesions.…”
Section: Molecular Biology Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As Ki67, HER1, and HER2, members of the epidermal growth factor receptor (HER) family are also up regulated in prostate cancer [ 111 , 112 ]. Reports have indicated a gain in the number of copies of the HER2 gene, which results in frequent overexpression of the protein not only in prostate tumors [ 113 ] but also in PIA [ 111 ]. Faleiro et al [ 111 ] detected mRNA of the HER1 gene in all evaluated cases of canine PC although present in normal tissue and pre-neoplastic lesions.…”
Section: Molecular Biology Of Prostate Cancermentioning
confidence: 99%
“…Reports have indicated a gain in the number of copies of the HER2 gene, which results in frequent overexpression of the protein not only in prostate tumors [ 113 ] but also in PIA [ 111 ]. Faleiro et al [ 111 ] detected mRNA of the HER1 gene in all evaluated cases of canine PC although present in normal tissue and pre-neoplastic lesions. Thus, these results reaffirm the idea that these receptors are involved in carcinogenesis and tumor development in the canine prostate.…”
Section: Molecular Biology Of Prostate Cancermentioning
confidence: 99%
“…High ex-pression levels of ERBB2 have been described in canine PC [ 17 ]. In a larger study investigating 25 canine PC, eight cases showed high EGFR expression, whereas 21 samples overexpressed ERBB2 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%